A New Copy of Baki's Divan and Baki's Poems That Are Not in Divan Publications - KÖKSAL, MEHMET FATİH (Ahmet Yesevi Üniversitesi, 2023)
The most brilliant period of classical Turkish poetry was the 16th century; the science, art and literature center of the 16th century was Istanbul; and the greatest poet of the period in Istanbul was Baki. Baki was known as "the sultan of poets " in his time. His poems , and especially his ghazals, were recorded in hundreds of poetry collections (mecmua) besides the manuscripts of his Divan. Baki's unpublished poems may be found in mostly poetry collections and in some Divan copies. In a copy of Bakis' Divan, which is in the personal library of M. Fatih Koksal, there are 20 unknown poems of Baki, 6 of which are ghazals, 1 of which are kit'a, and 13 of which are matla-mufred. Another interesting feature of the Koksal's copy is that 24 imitations (nazire) of 17 poets, some of which are not mentioned in the sources, were recorded in the margins. In this article, after evaluating the existence of Baki's poems that are included in some poetry collections but not in Divan copies, the said Divan copy will be introduced and the transcripted text of 20 unpublished poems will be published. The first couplets (matla') of the poems that are not found in the divan copies but have been brought to light by some publications will also be included.
Bâkî Dîvânı’nın Yeni Bir Nüshası ve Bâkî’nin Dîvân Neşirlerinde Bulunmayan Şiirleri
Keywords: Baki; Ghazal; Unkown Poems; Baki's Divan; Classical; Turkish Literature